Dimension linguistique, discursive et intellectuelle de la rédaction de texte académique en langue étrangère. Exemple des résumés de mémoires de licence et de master à la philologie française - Grabowska, Monika; Ucherek, Witold (Studia Romanica Posnaniensia, 2022)
The article focuses on the French summaries of BA & MA theses written by students of French philology at the University of Wrocław between 2015 and 2020. The objective is to determine to what extent the linguistic, discursive and intellectual dimensions of this short academic text constitute, for the students, a source of challenges during the writing process. The general conclusion is that very often the summary of a diploma thesis looks like a report detailing the activities of the student, instead of summarizing an intellectual trajectory and informing of the results of the research.